Transforming Drug Discovery: Leveraging Deep Learning and NLP for Accelerated Drug Repurposing through Text Mining in Biomedical Literature - Thakur, Abhishek; Thakur, Gopal Kumar; Khan, Naseebia; Kulkarni, Shridhar (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Drug repurposing or drug repositioning aims to find new uses for existing drugs, providing a faster and more cost-effective approach to drug development compared to traditional methods. Rapid advancements in deep learning and natural language processing (NLP) methods present new opportunities to accelerate drug repurposing through automated analysis of biomedical literature. This paper provides a comprehensive review of recent applications of deep learning and NLP for drug repurposing through text mining of biomedical corpora. We describe the motivations, challenges, and trends in this exciting field, summarize key techniques, and present illustrative case studies. Promising directions for continued research are also discussed. Overall, this paper demonstrates how deep learning and NLP are transforming drug discovery by enabling large-scale mining of biomedical text to uncover hidden relationships between drugs, diseases, targets, and mechanisms.